THE CURRENT STATUS OF INTELLIGENT (SMART) CONTROL SYSTEMS OF ELECTRIC MACHINES (Proceedings of International Educators Conference, 2023)
Before getting into the main content of the treatise, we need to define the concept of "intellect" in general. It seems that this concept can be explained on the basis of a simple rule, but we cannot. because, at present, there is no clear opinion about "intellect" and "Artificial intelligence". Scientists who create this concept in different fields of science have different interpretations, there is no uniformity in their thinking. Therefore, we will try to explain the content of these concepts to the reader.